Diversified social cognition in temporal lobe epilepsy. (25th January 2021) - Giovagnoli, Anna Rita; Parente, Annalisa; Ciuffini, Roberta; Tallarita, Giulia Maria; Turner, Katherine; Maialetti, Andrea; Marrelli, Alfonso Mauro; Pucci, Barbara; ,
Abstract : Objectives: In an integrated model of social cognition (SC), the theory of mind (ToM), the recognition of behavior in social situations (RBSS), empathy, and sensitivity to moral and conventional rules (SMCR) cooperate in generating mental representations of the interpersonal relationships. The aim of this study was to extend our knowledge of the SC of temporal lobe epilepsy (TLE) patients by characterizing its various aspects and predictors. Materials and Methods: Fifty adult patients with TLE and 50 healthy controls were assessed using ToM, RBSS and SMCR neuropsychological tests, the Empathy Questionnaire, and the psychopathology Symptoms Check List 90R (SCL90‐R). Results: Patients and controls were similar in terms of occupation, income level, age, sex, marital status and the number of family members. Multivariate analysis of variance with demographic variables as the covariates showed that they were similar in SMCR and empathy. The patients, conversely, had lower ToM and RBSS scores, and higher scores on the SCL90‐R psychoticism, depression, paranoid ideation, obsessive‐compulsive, somatization and anxiety scales. Impaired RBSS was predicted by psychopathological symptoms, income level, schooling and the duration of epilepsy; ToM related to TLE laterality, seizure frequency and epilepsy duration. Conclusions: In adult patients with TLE, SC is simultaneously partially impaired and partially preserved, and the fact this is associated with clinical, demographic and psychological variables suggests that SC depends on the integrity of the temporal lobe and the interconnected brain regions, as well as psychosocial stimuli. This approach may contribute to clarify the neurobehavioural phenotype of TLE.